Between the Reconstruction of Utopia and the Renovation of Dystopia: Details to the Architectural Portrait of Moscow in the Film The Master and Margarita (2024) - Dedkov Oleg M. (Художественная культура)
The article is devoted to the visual image of Moscow in the film The Master and Margarita (2024), directed by M. Lokshin and based on M. Bulgakov’s novel of the same name. The analysis focuses on the architectural images of the real and project-level buildings depicted in the film, their relationship to the socio-cultural context of the novel, the real Moscow of the 1930s, and the imaginary pre-war Stalin’s Moscow. The text contains references to films that actively used the image of the pre-war Moscow architectural utopia and various literary and architectural allusions related to the director’s view of the plots and images of the source novel.